2012
DOI: 10.1149/2.005302eel
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Poly(acrylic acid) with Polycarbodiimide as Advanced Binder for Si/Graphite Composite Negative Electrodes in Li-Ion Batteries

Abstract: Cross-linked poly(acrylic acid) (PAA) with polycarbodiimide (PCD) is utilized as a binder for the Si/graphite composite electrode. Cross-linkage of PAA can be modulated by the addition of the PCD as a cross-linker into the slurry. Compared to PAA binder, initial reversible capacity of Si/graphite composite electrodes is increased with suppressed electrolyte decomposition by the use of cross-linked PAA. The electrode adhesion strength onto current collector is increased by the cross-linking of PAA with PCD. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…Moreover, the retention depends on the amount of added cross-linkers, which agrees with the previous result of the polycarbodiimide cross-linkage. 7 As a result, the moderate cross-linkage attains the better capacity retention, and 10CLPAH is the most optimum binder among them. Figure 3d further compares the cyclability with the NaOH-neutralized binders.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the retention depends on the amount of added cross-linkers, which agrees with the previous result of the polycarbodiimide cross-linkage. 7 As a result, the moderate cross-linkage attains the better capacity retention, and 10CLPAH is the most optimum binder among them. Figure 3d further compares the cyclability with the NaOH-neutralized binders.…”
Section: Resultsmentioning
confidence: 98%
“…5 Furthermore, PAH binders with cross-linkage between two carboxylic groups with polycarbodiimide efficiently improved the lithiation performance of Si. 7 The cross-linkage proceeded in organic solvent during slurry process. In this study, we prepare a new water-soluble crosslinked binder, synthesized by copolymerization of acrylic acid with coexistence of crosslinker, diallyl ether, and demonstrate the battery performance of silicon-graphite electrodes with the copolymers.…”
mentioning
confidence: 99%
“…They demonstrated that the resulting hierarchical hydrogel framework provides a continuous electrically conductive polyaniline (PANi) network, binding with the Si surface via crosslinker hydrogen bonding with phytic acid or electrostatic interaction between the positively charged PANi doped with phytic acid and the negatively charged surface oxide (-Si-O-) on the Si, with a porous space for a large volume expansion of the Si nanoparticles. The Si nanoparticle-PANi hydrogel composite is fabricated by solution-phase synthesis by mixing Si nanoparticles with phytic acid and an aniline monomer in water to produce a suspension [43]. The SiPANi composite electrode exhibited relatively stable cycling performance compared to other samples and delivered a high Li extraction capacity of ~1,200 mAh g -1 after 1,000 cycles ( Fig.…”
Section: Crosslinked Polymeric Bindersmentioning
confidence: 99%
“…20(b)). Komaba et al reported crosslinked PAA with polycarbodiimide (PCD) as a binder for a Si/graphite composite anode [43]. They demonstrated the positive effect of PCD as a crosslinker for a PAA binder on the electrochemical performance of Si/graphite anodes.…”
Section: Crosslinked Polymeric Bindersmentioning
confidence: 99%
See 1 more Smart Citation